Dose‐Dependent Increases in Ellagitannin Metabolites as Biomarkers of Intake in Humans Consuming Standardized Black Raspberry Food Products Designed for Clinical Trials. Issue 10 (17th March 2020) - Roberts, Kristen M.; Grainger, Elizabeth M.; Thomas‐Ahner, Jennifer M.; Hinton, Alice; Gu, Junnan; Riedl, Ken; Vodovotz, Yael; Abaza, Ronney; Schwartz, Steven J.; Clinton, Steven K.
Abstract : Scope: Black raspberry (BRB) phytochemicals demonstrate anti‐carcinogenic properties in experimental models, including prostate cancer. Two BRB foods, a confection and nectar, providing a consistent and reproducible product for human clinical studies are designed and characterized. Methods and results: Men with clinically localized prostate cancer are sequentially enrolled to a control group or one of four intervention groups (confection or nectar, 10 or 20 g dose; n = 8 per group) for 4 weeks prior to prostatectomy. Primary outcomes include: safety, adherence, and ellagitannin metabolism. Adherence to the intervention is >96%. No significant (≥grade II) toxicities are detected. Urinary urolithins (A, B, C, and D) and dimethyl ellagic acid (DMEA) quantified by Ultra high performance liquid chromatography tandem mass spectroscopy (UPLC/MS/MS) indicate a dose‐dependent excretion yet heterogeneous patterns among men. Men in the BRB confection groups have greater urinary excretion of the microbial urinary metabolites urolithin A and DMEA, suggesting that this food matrix provides greater colonic microflora exposure. Conclusion: Fully characterized BRB confections and nectar are ideal for food‐based large phase III human clinical studies. BRB products provide a bioavailable source of BRB phytochemicals, however large inter individual variation in polyphenol metabolism suggests that host genetics, microflora, and other factors are critical to understanding bioactivity and metabolism. Abstract : Two black raspberry foods, a nectar and confection, are developed for clinical trials influencing health and disease outcomes. A four‐week pre‐prostatectomy study assesses safety, adherence, and metabolism (UPLC/MS/MS) of black raspberry ellagitannins in men with prostate cancer. Urinary metabolites (urolithin A and dimethyl ellagic acid) are biomarkers of intake. Black raspberry nectar and confections are appropriate for future clinical studies.